Association between the body roundness index and osteoarthritis: evidence from NHANES - Ke, Tiancheng; Lai, Jianqiang; Li, Xianmin; Liu, Fuqian; Liu, Wei; Zhong, Chengfan (Frontiers in Medicine, 2024)
The Body roundness index (BRI) is a quantitative measure used to evaluate the presence of obesity and the distribution of body fat. However, the relationship between the BRI and osteoarthritis (OA) is still unclear. The aim of this study is to examine the relationship between the BRI and the occurrence of OA.Cross-sectional analysis was employed in this study, which analyzed data from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018. A variety of variables were incorporated into this investigation, which employed logistic regression analysis to assess the correlation between BRI and OA. The robustness of the results and the impact of stratification variables were evaluated through subgroup and sensitivity analyses. To evaluate the ability of the BRI to predict OA, receiver operating characteristic (ROC) analysis was implemented.The analysis included 19,717 participants. Participants with OA had significantly greater BRI than did those without OA. Logistic regression analysis revealed a statistically significant and positive correlation between BRI and OA (OR=1.18, 95% CI=1.15-1.21, p-value <0.001). Despite the complete adjustment for covariates, this association remains stable (OR = 1.10, 95% CI=1.04-1.17, p-value = 0.002). The results were corroborated by subgroup and sensitivity analyses, which demonstrated their robustness. Moreover, the BRI exhibited a greater prediction accuracy for OA than did BMI.BRI and OA are significantly associated in adults in the United States. The risk of developing OA may be elevated by elevated BRI levels. Monitoring BRI levels is essential for preventing or reducing the prevalence and advancement of OA.